Validity and Reliability of the Intrinsic Motivation Inventory Subscales within a self-directed blended learning environment - Dorothy Joy Laubscher; Chantelle Bosch (Universitas Negeri Makassar, 2024)
Blended learning environments, where face-to-face and online learning are integrated, are gaining traction in education, offering opportunities for self-directed learning and intrinsic motivation. This study explores the validity and reliability of the Intrinsic Motivation Inventory (IMI) in a self-directed blended learning context. A cross-sectional design involving 651 final-year teacher students reveals high reliability in interest/enjoyment, competence, and autonomy subscales (Cronbach’s alpha: 0.94, 0.94, 0.85, respectively). A confirmatory factor analysis (CFA) indicates a favourable model fit (TLI: 0.970, CFI: 0.975, RMSEA: 0.056), reinforcing the IMI's appropriateness in this setting. Factor loadings demonstrate convergent validity, which emphasises the importance of interest, competence, and autonomy in fostering intrinsic motivation. The use of convenience sampling and the exclusion of the belonging factor due to low reliability are identified as limitations in this study. Future research might explore the use of diverse populations, longitudinal studies, additional constructs, and qualitative insights. This study contributes to educational research by validating the IMI in self-directed blended learning, emphasising the need for engaging experiences, competence, and autonomy to enhance intrinsic motivation.